2020
DOI: 10.1152/jn.00163.2020
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor patterns during obstacle avoidance in children with cerebral palsy

Abstract: We investigated how early injuries to developing brain affect the interaction of locomotor patterns with the voluntary action required by obstacle clearance. This task requires higher cognitive load and specific anticipatory sensorimotor integration than more automated steady-state gait. To this end, we compared the adaptive gait patterns during obstacle clearance in 40 children with cerebral palsy (CP) (24 diplegic, 16 hemiplegic, 2-12 years) and 22 typically developing (TD) children (2-12 years) by analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…In general, children with CP have difficulties in clearing an obstacle, being slower in approach and crossing speed along with unsteadiness of gait and balance adaptations of the trunk control (Law and Webb, 2005;Malone et al, 2016). For instance, in a recent study (Cappellini et al, 2020) we showed that about 30% of children with bilateral CP failed to perform the task (they stopped before the obstacle, performed lateral obstacle avoidance, stumbled or stepped onto the obstacle). Interestingly, they had mostly posterior lesions of the brain (Cappellini et al, 2020), in relation to their deficits in the anticipatory visuomotor control and important role of parietal lobe activity in visually planning gait adaptations (Drew et al, 2008;Lajoie et al, 2010;Drew and Marigold, 2015).…”
Section: Adaptive Gait Control In Cpmentioning
confidence: 97%
See 4 more Smart Citations
“…In general, children with CP have difficulties in clearing an obstacle, being slower in approach and crossing speed along with unsteadiness of gait and balance adaptations of the trunk control (Law and Webb, 2005;Malone et al, 2016). For instance, in a recent study (Cappellini et al, 2020) we showed that about 30% of children with bilateral CP failed to perform the task (they stopped before the obstacle, performed lateral obstacle avoidance, stumbled or stepped onto the obstacle). Interestingly, they had mostly posterior lesions of the brain (Cappellini et al, 2020), in relation to their deficits in the anticipatory visuomotor control and important role of parietal lobe activity in visually planning gait adaptations (Drew et al, 2008;Lajoie et al, 2010;Drew and Marigold, 2015).…”
Section: Adaptive Gait Control In Cpmentioning
confidence: 97%
“…For instance, in a recent study (Cappellini et al, 2020) we showed that about 30% of children with bilateral CP failed to perform the task (they stopped before the obstacle, performed lateral obstacle avoidance, stumbled or stepped onto the obstacle). Interestingly, they had mostly posterior lesions of the brain (Cappellini et al, 2020), in relation to their deficits in the anticipatory visuomotor control and important role of parietal lobe activity in visually planning gait adaptations (Drew et al, 2008;Lajoie et al, 2010;Drew and Marigold, 2015). Remaining children with CP (∼70%), who succeeded with obstacle clearance, performed the task significantly slower than age-matched TD children, demonstrating a high foot lift of the trailing (unseen) limb, smaller range of motion and muscle moments of the distal (ankle) joint ( Figure 5A, left panels), and limited adaptation of task-relevant activity of hamstring muscles timed to the voluntary task of foot lift over the obstacle (Cappellini et al, 2020).…”
Section: Adaptive Gait Control In Cpmentioning
confidence: 98%
See 3 more Smart Citations